2021
DOI: 10.1111/aor.14038
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of estradiol copreservation against kidney ischemia‐reperfusion injury

Abstract: Ischemia-reperfusion injury (IRI) is the major cause of delayed graft function (DGF) during the posttransplantation period. Estradiol (E2) prevents IRI-induced kidney dysfunction and tissue injury. However, many side effects limit E2's in vivo application. Recent evidence uncovers E2's expanded use in the field of transplantation.We aimed to study if and how E2 exerts protective activity during the period of kidney organ preservation. The autologous kidney transplant model in rats was first established. Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(64 reference statements)
0
0
0
Order By: Relevance
“…In young females, estrogens play a predominantly protective role, ameliorating the consequences of IRI while the protective effects of estrogens may be less pronounced with aging (54,66). In support, pre-clinical studies investigating the effects of selective estrogen receptor modulators and treatment suggest that the loss of protection in aging could at least in part be preserved (55,67).…”
Section: Aging and Biological Sex Affecting Ischemia Reperfusion Inju...mentioning
confidence: 94%
See 1 more Smart Citation
“…In young females, estrogens play a predominantly protective role, ameliorating the consequences of IRI while the protective effects of estrogens may be less pronounced with aging (54,66). In support, pre-clinical studies investigating the effects of selective estrogen receptor modulators and treatment suggest that the loss of protection in aging could at least in part be preserved (55,67).…”
Section: Aging and Biological Sex Affecting Ischemia Reperfusion Inju...mentioning
confidence: 94%
“…Female recipient sex mainly attributed to the influence of estrogens has been shown to protect against IRI ( 52 54 ). A variety of pre-clinical studies in kidney, heart, and livers has shown a protective role of estrogens against IRI ( 55 59 ). Underlying pathways, although only incompletely understood include the influence of estrogens on mitochondrial activity, the expression of antioxidant enzymes, and inflammatory responses subsequent to IRI ( 58 , 60 , 61 ).…”
Section: Aging and Biological Sex Affecting Ischemia Reperfusion Inju...mentioning
confidence: 99%